Construction and validation of a U-type finite element model of an osteoporotic vertebral compression fracture - Li, Pengfei; Mu, Jihao; Wang, Zhao; Zhang, Xiaochong; Zhang, Yingze; Liu, Dengxiang; Li, Ao (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAn osteoporotic vertebral compression fracture (OVCF) is recognized as a common complication of osteoporosis. Biomechanical alterations in the affected and adjacent vertebrae have a significant influence on patient symptoms, treatment strategies, and clinical outcomes. Nevertheless, establishing an accurate model of OVCF remains a highly challenging task. In this study, a novel finite-element model of OVCF was developed and validated, and a comprehensive biomechanical analysis was conducted.MethodsComputed tomography data of the thoracolumbar spine (T12–L2) were collected from an OVCF patient and a healthy volunteer to establish the OVCF and normal models, respectively. Based on the normal model, U-type, V-type, and double-V-type finite element models were constructed. Intervertebral disks and articular cartilage were generated through a combination of appropriate materials and assemblies, followed by the development of three-dimensional finite-element biomechanical models. The magnitude and distribution of stress and displacement in these three models were evaluated and compared with those of the OVCF model under various directions of motion.ResultsIn the force distribution contour diagrams, the U-type model at the T12 vertebra most closely resembled the OVCF model, particularly in the directions of forward flexion, backward extension, left lateral bending, and left rotation. Force distribution patterns and stress concentration areas in all six directions were generally consistent between the U-type and OVCF models. At the L2 vertebra, the U-type model demonstrated the greatest similarity to the OVCF model in the direction of left lateral bending. At the T12/L1 intervertebral disk, no significant differences in the force distribution were observed among the four models. At the L1/2 intervertebral disk, the U-type and OVCF models showed the closest correspondence in the direction of forward flexion. In the displacement contour diagrams, the maximum displacements of the U-type model were found to be 1.7876 mm (forward flexion), 6.1564 mm (posterior extension), 4.6520 mm (left lateral bending), 6.2224 mm (right lateral bending), 3.4119 mm (left rotation), and 3.1601 mm (right rotation). Notably, in the direction of left lateral bending, the U-type model most closely approximated the displacement distribution of the OVCF model.ConclusionThe U-type finite-element model more accurately reproduces the biomechanical characteristics of OVCF and demonstrates high applicability.